THE FOREIGN EXPERIENCE OF INCREASING THE COMPETITIVENESS OF THE REGIONAL ECONOMY AND THE PROSPECTS OF ITS USE IN THE NATIONAL ECONOMY (American Journal of Interdisciplinary Research and Development, 2024)
This article explores the strategies employed by various countries to enhance the competitiveness of their regional economies. By examining successful foreign experiences such as cluster development in the USA, special economic zones in China, vocational training in Germany, innovation ecosystems in Israel, infrastructure development in Singapore, regional branding in Italy, and sustainable development in Nordic countries, the article identifies key elements that contributed to their success. The potential application of these strategies in the national economy is discussed, highlighting the importance of tailoring policies to local contexts, fostering public-private partnerships, investing in human capital, promoting innovation, enhancing infrastructure, and integrating sustainable practices.